Thermal management of shelter building walls by PCM macro-encapsulation in commercial hollow bricks - Izadi, Masoud; Taghavi, Seyede Fateme; Neshat Safavi, Seyed Hossein; Afsharpanah, Farhad; Yaïci, Wahiba (Case studies in thermal engineering, 2023)
Maintaining building indoor temperature within comfort zone has been identified as one of the major reasons for energy consumption. The incorporation of phase change materials (PCMs) in various regions in buildings is introduced as a solution that can significantly reduce energy consumption. In the current research, a three-dimensional computational fluid dynamics approach is taken to evaluate the influence of incorporating three PCMs from the Rubitherm® RT line (RT15, RT18, and RT22) in two widespread commercial hollow brick types in Iran for keeping the indoor environment of a shelter warm in a cold climate. These enhanced bricks are compared with their solid and hollow counterparts. Furthermore, efforts were made to examine various configurations of these PCMs, with melting temperatures in obedience or contrast with the thermal stratification of the bricks. Several combinations of the PCM with air layers are studied to assess the best way to place the air and PCM layers. It was found that the RT18 PCM-filled brick can present lower heat fluxes than the hollow one for over 42 h. Also, the findings showed that RT22 PCM-filled brick can provide 66.79% lower average heat flux compared to the hollow brick for the first 24 h of the process. •Incorporation of three PCMs in two conventional clay bricks was examined.•Brick and PCM types, PCM arrangement, and combination with air layers were tested.•Heat flux and energy consumption reductions as well as energy saving were studied.•RT18 PCM-filled brick offered lower heat fluxes than the hollow one for over 42 h.•RT22 PCM-filled brick provided an energy saving of 66.79% for the first 24 h.